PERAN AYAH DALAM PENGASUHAN ANAK: TINJAUAN LITERATUR KESEJAHTERAAN PSIKOLOGIS DARI PERSPEKTIF ISLAM - Azahra Hardi Cusinia (Jurnal Keluarga Sehat Sejahtera, 2025)
The presence of fathers in childrearing is increasingly recognized as a crucial factor in supporting children’s psychological well-being. However, paternal roles are often narrowly understood as economic providers, while emotional, behavioral, and spiritual involvement remains underexplored, particularly within Muslim family contexts. This article aims to examine the role of father presence in parenting and its implications for children’s psychological well-being from an Islamic perspective. The study employs a narrative literature review by analyzing relevant empirical and conceptual studies on father involvement, children’s psychological well-being, and Islamic values in family parenting. The findings indicate that high-quality father involvement contributes positively to children’s emotional regulation, adaptive behavior, and cognitive development. From an Islamic perspective, fathers are positioned as central figures in parenting with moral and spiritual responsibilities that serve as protective factors in fostering children’s psychological resilience. These findings highlight the importance of active and meaningful father involvement in parenting to support children’s psychological well-being holistically.